2023
DOI: 10.2147/ccid.s398547
|View full text |Cite
|
Sign up to set email alerts
|

(–)-Epigallocatechin-3-Gallate Protects Human Skin Fibroblasts from Ultraviolet a Induced Photoaging

Abstract: Background Ultraviolet (UV) is a common stressor of skin and repeated UVA radiation contributes to photoaging. (–)-Epigallocatechin-3-Gallate (EGCG), as the major polyphenol that is found in green tea, and catechins and have shown considerable antioxidant capacity. Purpose Our study aims to explore the effects of EGCG on UVA-induced skin photoaging process and associated mechanisms. Methods In this study, human skin fibroblasts (HSFs) were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
9
1
1
Order By: Relevance
“…Despite no statistical significance being observed in our MR analysis, some studies have reported tea intake is a protective agent for facial skin aging. 7,[46][47][48][49][50][51] Tea extracts have been found to improve wrinkles and attenuate light-induced skin aging in mouse models. 46,47 However, a randomized controlled trial in vivo found no statistically significant differences in skin aging after 2 years of supplementation with oral tea polyphenols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite no statistical significance being observed in our MR analysis, some studies have reported tea intake is a protective agent for facial skin aging. 7,[46][47][48][49][50][51] Tea extracts have been found to improve wrinkles and attenuate light-induced skin aging in mouse models. 46,47 However, a randomized controlled trial in vivo found no statistically significant differences in skin aging after 2 years of supplementation with oral tea polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…7,47 The primary active ingredient of tea polyphenols, Epigallocatechin gallate (EGCG), has been identified as a potential anti-aging ingredient due to its function to scavenge ROS, inhibit the expression of MMPs, and increase collagen synthesis. [48][49][50][51] Studies have revealed inconsistent associations between alcohol intake and facial skin aging. [8][9][10][53][54][55] Some studies revealed that especially with heavy alcohol intake.…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al . [ 48 ] observed significant telomere shortening in human skin fibroblasts following exposure to UVA radiation. Marion et al .…”
Section: Mechanisms Of Skin Agingmentioning
confidence: 99%
“…Among these, EGCG is the major component of green tea polyphenols, which have been studied in many beneficial effects, such as anti-inflammatory, antioxidative, antimicrobial, and anticancer effects [ 9 ]. The study reported that EGCG could be a potential strategy in preventing human skin fibroblasts (HSF) photoaging induced by UVA radiation, is closely related to its powerful antioxidant effects to regulate the expression of related genes, like tissue inhibitor of metalloproteinase-1 (TIMP-1), p66 [ 10 ]. EGCG counters UVB-mediated phototoxicity via inhibition of the epidermal growth factor receptor in keratinocytes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%